The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1590/s1516-635x2007000300005
|View full text |Cite
|
Sign up to set email alerts
|

Performance of japanese quails fed feeds containing different corn and limestone particle sizes

Abstract: This study aimed at evaluating performance and egg quality of Japanese quails fed feeds containing different corn and limestone particle sizes. A total number of 648 birds in the peak of production was distributed in a random complete block experimental design, using a 2x3 factorial arrangement (2 corn particle sizes and 3 limestone particle sizes). Birds were designated to one of two blocks, with six replicates of 18 birds each. Mean geometric diameter (MGD) values used were 0.617mm and 0.723mm (corn fine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
(12 reference statements)
1
0
2
Order By: Relevance
“…The differences observed for FCR (Table 5) between the treatments were not statistically significant (P>0.05). The average values of FCR obtained in this study in terms of kg feed consumed to produce dozen eggs were comparatively higher than those reported by Berto et al, (2007) for Japaese quails (0.39 kg/dz) fed with feeds containing different corn and lime stone particles. This may be mainly due to adoptation of mixed sex rearing system during the experimental period.…”
Section: Feed Conversion Ratiocontrasting
confidence: 83%
“…The differences observed for FCR (Table 5) between the treatments were not statistically significant (P>0.05). The average values of FCR obtained in this study in terms of kg feed consumed to produce dozen eggs were comparatively higher than those reported by Berto et al, (2007) for Japaese quails (0.39 kg/dz) fed with feeds containing different corn and lime stone particles. This may be mainly due to adoptation of mixed sex rearing system during the experimental period.…”
Section: Feed Conversion Ratiocontrasting
confidence: 83%
“…The best egg-laying rates obtained in the present study were 81.67%; 86.67% and 88.33% respectively for GD 3, LD 2 and LD 3. These results corroborate those of [45]; [46]; [47]; [48] as well as [49]. These authors indeed obtained laying rates between 82% and 89.36% during a laying period of eight weeks (from the sixth to the fourteenth week).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the synergistic action resulting from the association of several protein sources in the A3 food has already been demonstrated by many researchers including Smith [33] who showed that various protein sources lead to better performance of spawn subjects. The daily egg laying rates obtained in quails in this study are lower than those obtained by Marques et al [34], Berto et al [35], Hassan [36] and Abdel-Azeem [30]. who worked respectively on quails during a period ranging from the 6 th to the 14 th week.…”
Section: Discussioncontrasting
confidence: 78%